Nutritional Obesity and its Relationship to Body Mass Index and Resting Heart Rate among Practicing and Non-Practicing Students/University of Zakho; A Comparative Study - Abdulsatar, Athraa Abdulelah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This comparative study investigates the relationship between nutritional obesity, body mass index (BMI), and resting heart rate (RHR) among practicing and nonpracticing students at the University of Zakho. The research aimed to identify the correlation between BMI and variables such as weight, height, and resting pulse, as well as to determine if there are significant differences in BMI and RHR between practicing and nonpracticing students. The study employed a descriptive approach with a comparative method of correlational relationships, using a sample of 71 students from the Departments of Physical Education and Sports Sciences and General Psychology. Key findings include a strong positive correlation between BMI and body weight, a positive correlation between BMI and RHR, and a non-significant correlation between BMI and height. The study also revealed significantly higher mean BMI and RHR in the nonpracticing group compared to the practicing group. These results highlight the beneficial effects of regular physical activity on weight management, obesity prevention, and cardiovascular fitness. The insights gained from this study can inform the development of targeted interventions and health promotion strategies to address obesity-related concerns among university students.